2002
DOI: 10.1079/bjn2002661
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oligofructose or dietary calcium on repeated calcium and phosphorus balances, bone mineralization and trabecular structure in ovariectomized rats

Abstract: We investigated the effects of dietary oligofructose and Ca on bone structure in ovariectomized rats, using microradiography and histomorphometry. Ninety-six animals were allocated to seven experimental groups: G1, sham-operated; G2-G7, ovariectomized. Semi-purified diets containing 5 g Ca/kg (recommended content) without oligofructose (G1, G2) or with 25, 50 or 100 g oligofructose/kg (G3, G4, G5) or 10 g Ca/kg (high content) without oligofructose (G6) or with 50 g oligofructose/kg (G7) were fed for 16 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 42 publications
2
58
1
Order By: Relevance
“…A crosstalk between osteoblasts and adjacent endothelial cells in view of altering the vascularity of the bone-forming site is also possible. The expression of VEGF can be enhanced by several growth factors, such as PGE2, FGF-2, TGF-b1, IGF-1, and BMP-4, -2, and -6 [25]. Basic fibroblast growth factor stimulates VEGF release through p42/p43 mitogenactivated protein (MAP) kinase in osteoblasts and negatively regulates it by p38 MAP kinase [28].…”
Section: Discussionmentioning
confidence: 99%
“…A crosstalk between osteoblasts and adjacent endothelial cells in view of altering the vascularity of the bone-forming site is also possible. The expression of VEGF can be enhanced by several growth factors, such as PGE2, FGF-2, TGF-b1, IGF-1, and BMP-4, -2, and -6 [25]. Basic fibroblast growth factor stimulates VEGF release through p42/p43 mitogenactivated protein (MAP) kinase in osteoblasts and negatively regulates it by p38 MAP kinase [28].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the efficiency of measuring bone metabolism biomarkers has been demonstrated (van Coeverden et al, 2002). Studies in diverse animal models have shown the beneficial effect of inulin and oligofructose in the colonic epithelium, stimulating proliferation in the crypts, increasing the concentration of polyamines, changing the profile of mucins and modulating endocrine as well as immune functions (Roberfroid, 2005;Budiño et al, 2005), and on calcium absorption and bone mass (Roberfroid, 2002;Scholz-Ahrens et al, 2002;Cashman, 2003;Kruger et al, 2003;Lobo et al, 2006). This was also observed in adolescents (Griffin et al, 2002), showing a significant increase in calcium absorption with oligofructose-enriched inulin supplementation (8 g/d of Synergy1).…”
Section: Discussionmentioning
confidence: 99%
“…Although the small intestine is the principal site of calcium absorption in humans, significant amounts may be absorbed throughout the length of the gut, consequently maximising of colonic effects is desirable. Numerous animal studies have indicated that prebiotics increase calcium, zinc and magnesium absorption from the colon (Delzenne et al, 1995;Younes et al, 2001;Coudray et al, 2003;Raschka & Daniel, 2005a), resulting in increased bone density and bone trabecular structure (Ohta et al, 2002;Scholz-Ahrens et al, 2002;Raschka & Daniel, 2005b). Raschke and Daniel (2005b) reported increased absorption, retention and femur content of calcium, zinc and magnesium in a rat model only when the basic diet of the control group contained no intrinsic fructans and when the mineral demand was particularly high, as during growth.…”
Section: Increased Mineral Absorptionmentioning
confidence: 99%
“…(reviewed recently by Scholz-Ahrens et al, 2007). The intake of prebiotics acidifies the intestinal contents, which aids the solubilisation of minerals .…”
Section: Modulation Of the Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation